Bioactive Terpenes from Marine Sponges and Their Associated Organisms - Yuan Yuan; Yu Lei; Muwu Xu; Bingxin Zhao; Shihai Xu (Marine Drugs)
In recent years, marine natural products have continued to serve as a pivotal resource for novel drug discovery. Globally, the number of studies focusing on Porifera has been on the rise, underscoring their considerable importance and research value. Marine sponges are prolific producers of a vast array of bioactive compounds, including terpenes, alkaloids, peptides, and numerous secondary metabolites. Over the past fifteen years, a substantial number of sponge-derived terpenes have been identified, exhibiting extensive structural diversity and notable biological activities. These terpenes have been isolated from marine sponges or their associated symbiotic microorganisms, with several demonstrating multifaceted biological activities, such as anti-inflammatory, antibacterial, cytotoxic, anticancer, and antioxidant properties. In this review, we summarize 997 novel terpene metabolites, detailing their structures, sources, and activities, from January 2009 to December 2024. The structural features and structure-activity relationship (SAR) of different types of terpenes are broadly analyzed and summarized. This systematic and comprehensive review will contribute to the summary of and speculation on the taxonomy, activity profiles, and SAR of terpenes and the development of sponge-derived terpenes as potential lead drugs.